Iran architecture in Sassanid era - Karimi, Mitra (2008)
Considering science and technology developments and spread of communities and high speed of information transition, it's necessary to become hamonized with world developments. This will be along with transition of cultures, behaviours, different thoughts and life styles. Some of the culture exchanges cause improvement and completing our national culture, but others are incompatible with our regional culture. In addition to this, architecture is mixed with human life and usually related with culture, nature, world vision and thoughts of each nation every time. So we can consider it one of the best appearances of civilization and culture of each nation in any era. Iranian architecture has followed bases and criteria, coordinating with culture, life style, climate, economy and human necessities. It's a question in today's mixed architecture of Iran, especially in large cities, that why our multi thousand yaer culture and civilization can't solve the problem of updating the architecture with it's rich background and special ideas. Our country is one of the oldest civilizations of the world and there is architecture and stonecutting works belong to more than 7000 years before in several places in Iran, but multi thousand year history of Iran architecture is not studied well. Iranian architecture is divided in two parts: pre-Islam and post-Islam. Pre-Islam architecture belongs to Media, Achaemenid, Parthia and Sasanid eras. This document will be along with getting acquainted with culture and art, specially architecture of iran in Sassanid era, and history, theory bases and physical features. Of course this bases and criteria are hamonized with our today understanding of Sasanid buildings and studies done done in this field.